ANALISIS NILAI EKONOMI ISLAM PADA PELAKSANAAN ARISAN PERKAWINAN DI DESA SUNGAI KUNYIT DALAM KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - JOHAN JOHAN (CV. Adiba Aisha Amira, 2024)
Arisan is a tradition of Indonesian society from time to time until now. There are many types of social gatherings that have developed, one of which is a wedding social gathering which functions to facilitate the holding of wedding parties. This research has two problem formulations, namely: (1) How is the marriage gathering implemented in Sungai Kunyit Dalam Village? (2) What is the analysis of Islamic economic values on the practice of wedding gatherings in Sungai Kunyit Dalam Village? This research is field research with a descriptive qualitative approach. The research subjects were 10 (ten) people. Meanwhile, the object of research is the practice of wedding gatherings in Sungai Kunyit Dalam village, Sungai Kunyit sub- district, Mempawah district. The data collection techniques are using interviews, observation and documentation. The results of this research are: (1) The implementation of the marriage gathering is a conditional system, namely that the recipient of the marriage gathering must be a resident of the wedding party. The wedding gathering is held on Friday evening, exactly 7 days after the wedding party. In payments, there is a term known as